(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2024)
Fish otoliths from three localities in northern Italy (Piedmont), Grazzano, Rio Freddo di Albugnano and Valle Ceppi, ranging in age from late Oligocene (Chattian) to Early Miocene (Burdigalian) are described herein. One of these localities, Rio Freddo di Albugnano, straddles the Oligocene/Miocene boundary, and the otoliths are interpreted to reflect a late Oligocene age. The other two localities are from the upper Burdigalian (Lower Miocene). The otolith assemblages described herein complement previously described associations from the northern Mediterranean region and contain a total of 68 species-level taxa, 16 of which are new and 12 remain in open nomenclature. The upper Oligocene strata yielded 24 species and the Lower Miocene strata 48 species; four species are shared. The results are compared with previous studies and discussed. Deepwater taxa are abundant in the assemblages, particularly those pertaining to the mesopelagic family Myctophidae. The otolith assemblage fills a stratigraphic gap in the record of this family in Europe and thus contributes to refinement of stratigraphic ranges of myctophid species. The otolith assemblages are also compared with coeval assemblages known from other regions of the world and their paleobiogeographic significance is discussed. Myctophid species particularly show often a very wide geographic distribution pattern across ocean basins during the Miocene similar to that characteristic of this family today. In combination with refined stratigraphic ranges of myctophid species, this wide geographic distribution could ultimately become useful as a biostratigraphic tool in a supra-regional perspective. The following 15 taxa are described herein as new: Bathycongrus delfinoi n. sp., Japonoconger asper n. sp., Ariosoma ceppiensis n. sp., Eokrefftia paviai n. sp., Diaphus cuneatus n. sp., Diaphus pertinax n. sp., Diaphus hastaensis n. sp., Lampanyctus rostratus n. sp., Nezumia marramai n. sp., Coryphaenoides delapierrei n. sp., Glyptophidium monoceros n. sp., Giuntellia n. gen. singularis n. sp., Epigonus liguriensis n. sp., Cepola macilenta n. sp., Owstonia rhomboidea n. sp.